Altered Gray Matter Volume and White Matter Integrity in College Students with Mobile Phone Dependence - Wang, Yongming; Zou, Zhiling; Song, Hongwen; Xu, Xiaodan; Wang, Huijun; d’Oleire Uquillas, Federico; Huang, Xiting (Frontiers in Psychology, 2016)
Mobile phone dependence (MPD) is a behavioral addiction that has become an increasing public mental health issue. While previous research has explored some of the factors that may predict MPD, the underlying neural mechanisms of MPD have not been investigated yet. The current study aimed to explore the microstructural variations associated with MPD as measured with functional Magnetic Resonance Imaging (fMRI). Gray matter volume (GMV) and white matter (WM) integrity (four indexes: fractional anisotropy, FA; mean diffusivity, MD; axial diffusivity, AD; and radial diffusivity, RD) were calculated via voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) analysis, respectively. Sixty-eight college students (42 female) were enrolled and separated into two groups (MPD group, N=34; control group, N=34) based on Mobile Phone Addiction Index (MPAI) scale score. Trait impulsivity was also measured using the Barrett Impulsivity Scale (BIS-11). In light of underlying trait impulsivity, results revealed decreased GMV in the MPD group relative to controls in regions such as the right superior frontal gyrus (sFG), right inferior frontal gyrus (iFG), and bilateral thalamus (Thal). In the MPD group, GMV in the above mentioned regions was negatively correlated with scores on the MPAI. Results also showed significantly less FA and AD measures of white matter integrity in the MPD group relative to controls in bilateral hippocampal cingulum bundle fibers (CgH). Additionally, in the MPD group, FA of the CgH was also negatively correlated with scores on the MPAI. These findings provide the first morphological evidence of altered brain structure with phone-overuse, and may help to better understand the neural mechanisms of MPD in relation with other behavioral and substance addiction disorders.